Study the effect of drought and salinity stresses on germination and early growth seedling of camelthorn native of Razavi Khorasan province (Alhagi maurorum) - Mohadeseh Shamsaddin Saied (علوم و فناوری بذر ایران, 2023)
Environmental stresses, including drought and salinity stress can play an important role in reducing plant growth and yield especially in the seedling establishment stage in arid and semi-arid climates of Iran.Therefore, identification of range plants tolerance to drought and salt is very important.To assay the effect of different concentrations of drought and salinity on germination and early growth of camelthorn(Alhagi maurorum) two experiments were performed separately in a completely randomized design with three replications in the laboratory of Bardsir Faculty of Agriculture, Shahid Bahonar University of Kerman.30 uniform seeds were sterilized with 10% sodium hypochlorite solution for 30 seconds and after washing the seeds three times with distilled water, they were placed in 9 cm Petri dishes on Whatman No. 2 filter paper.In the first experiment, polyethylene glycol solution (PEG6000) with concentrations of -1, -1.5 and -2 MPa was applied to obtain the osmotic potential, and in the second experiment, NaCl with concentrations of 100, 150 and 200 mM was used.Distilled water was also applied to make zero stress(control)in both experiments. Results showed that camelthorn seeds were able to germinate at -2 MPa of drought potential and 200 mM salinity potential.However, increasing drought and salinity stress significantly reduced germination percentage and rate, seed vigor index, seedling dry weight, shoot length, root length, shoot dry weight and root dry weight.Assessing the response of this plant to different levels of drought and salinity in the germination stage and early growth of seedling is important for forage production, soil protection and medicinal value